Comparative Effects of Generative Learning Strategies and 5E Strategies on Pre-Service Teachers’ Achievement of Integrated Science Concepts - Yao Donusem Asamoah; Eric Appiah-Twumasi; John Bosco Kwasi Fiave; Daniel Mamudu (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to investigate the comparative effects of generative learning strategy (GLS) and 5E strategy (5E-IS) on the academic achievement of pre-service teachers in integrated science. This study addressed two research questions and test one hypothesis at .05 level of significance. Methodology: The research employed a non-equivalent pre- and post-tests design followed by semi-structured interviews. A sample of 157 pre-service teachers were selected from two intact programmes of study. The main data collection instruments were pre- and post-tests, and interview schedule. Data was analysed using mean scores, adjusted means, percentages and with Analysis of Covariance (ANCOVA). Interview results were analysed using narratives. Main Findings: There was relative improvement in pre-service teachers’ performance taught with GLS and 5E-IS. Moreover, pre-service teachers instructed using generative learning strategies demonstrated superior performance compared to those in 5E strategy group (effect size = 0.32, p = 0.000, < 0.05). The interview data reveals that both generative and 5E strategies were perceived as beneficial and adaptable approaches that enhance understanding, retention, knowledge transfer across various contexts, and ultimately motivating learners throughout the learning process. Novelty/Originality of this study: The effectiveness of GLS and 5E-IS hold significant implications for curriculum design, instructional practices, and teacher preparation programmes. Understanding pedagogical approach which yields superior learning outcomes, enhances retention of scientific concepts, and teacher efficacy is key. Insights from this study may contribute to the on-going discourse surrounding best practices in science education, fostering continuous improvement and innovation in instructional methodologies.